(untitled) - Dixon, James Ray.; Werler, John E.; Werler, John E. (Austin, 2005)
"Field guide to all snake species in Texas with a color photo, range map, and information on identifying characteristics and behavior for each snake"--Provided by publisher.
Rev. ed. of: Texas snakes / John E. Werler and James R. Dixon. 1st ed. 2000.
Includes bibliographical references (p. 345-353) and indexes.
Keywords: Snakes; Texas